A Novel Supramolecular Assembly Film of Porphyrin Bound DNA: Characterization and Catalytic Behaviors Towards Nitric Oxide - Osamu Ikeda; Huangxian Ju; Jianping Lei (Sensors, 2005)
A stable Fe(4-TMPyP)-DNA-PADDA (FePyDP) film was characterized onpyrolytic graphite electrode (PGE) or an indium-tin oxide (ITO) electrode through thesupramolecular interaction between water-soluble iron porphyrin (Fe(4-TMPyP)) and DNAtemplate, where PADDA (poly(acrylamide-co-diallyldimethylammonium chloride) isemployed as a co-immobilizing polymer. Cyclic voltammetry of FePyDP film showed a pairof reversible FeIII/FeII redox peaks and an irreversible FeIV/FeIII peak at –0.13 V and 0.89vs. Ag|AgCl in pH 7.4 PBS, respectively. An excellent catalytic reduction of NO wasdisplayed at –0.61 V vs. Ag|AgCl at a FePyDP film modified electrode.Chronoamperometric experiments demonstrated a rapid response to the reduction of NOwith a linear range from 0.1 to 90 μM and a detection limit of 30 nM at a signal-to-noiseratio of 3. On the other hand, it is the first time to apply high-valent iron porphyrin ascatalyst at modified electrode for NO catalytic oxidation at 0.89 vs. Ag|AgCl. The sensorshows a high selectivity of some endogenous electroactive substances in biological systems.The mechanism of response of the sensors to NO is preliminary studied.